Herd-level heterogeneity of antimicrobial resistance in commensal Escherichia coli: A nationwide high-throughput survey of Australian pig herds - Sam Abraham; David Jordan; Marin Milotic; Shewli Mukerji; Yvette Pollock; Samantha Sterndale; David J. Hampson; Kittitat Lugsomya; Rebecca Abraham (Veterinary Microbiology, 2026)

Variation in cocaine responses across genetically diverse mouse strains - Malia Pollock; AbdulRahman Abbas; Hien M. Bui; Jay-Ho Chung; Yanchao Dai; Jack DiCola; Levi Goldberg; Savanna Hale; Carter Joyce; Emily Rubio; M Schoales; Owen Snyder-Smith; et al. (Psychopharmacology, 2026)

HPAI drives a fourfold increase in adult gannet mortality which requires two decades recovery time - Jude V. Lane; Jason Matthiopoulos; David Astins; Ian Cleasby; Keith C. Hamer; Kirsty A. Franklin; Ruth Jeavons; Liam P. Langley; Aly McCluskie; Greg Morgan; Lisa Morgan; Christopher J. Pollock; et al. (Biological Conservation, 2026)

Sampling microbial dynamics in the Salish Sea estuary: evaluating methods to capture cyanobacteria and cyanophage - Noelani R. Boise; Owen P. Leiser; Kristin Jones; Mahala Peter-Frank; Damon Leach; Stephen Crafton-Tempel; Peter Regier; Ruonan Wu; Conner Phillips; Margaret S. Cheung; Connah G. M. Johnson; Scott J. Edmundson; et al. (Frontiers in Marine Science, 2026)
Introduction Picocyanobacteria from the genera Prochlorococcus and Synechococcus thrive across the globe in aquatic environments, have relatively small genomes, and have growth dynamics regulated by both viral interactions and abiotic conditions, making them excellent model organisms for exploring host-pathogencoevolution. Methods We developed and refined methods to sample and sequence cyanobacteria, cyanophages, and measured features of their abiotic environment. Results The protocol described herein can successfully discriminate large-cell eukaryotic organisms, but size fractionation of picocyanobacteria appears to be affected by the presence of free DNA, multicellular structures, and abundant tycheposons. Our preferred final protocol from this exploratory effort included a combination of in-line and single vacuum flask filtrations, which reduced filtration processing time by over threefold in some cases compared to other tested methods, such as a fully in-line sequence or in-site filtrations. We successfully extracted an average of approximately 400–1200 ng for all filter fractions, with some variations between kits. Discussion The protocol described herein can successfully discriminate large-cell eukaryotic organisms, but size fractionation of picocyanobacteria appears to be affected by the presence of free DNA, multicellular structures, and abundant tycheposons.

Effects of repeated blocks of split-belt walking on locomotor adaptation, physiological arousal response and cortical activation - Kaya Yoshida; Shannon B. Lim; Lara A. Boyd; Janice J. Eng; Amy Schneeberg; Theodore J. Huppert; Courtney L. Pollock (Experimental Brain Research, 2026)

Values of protected area landscapes shape the behaviors of subsistence users in Interior Alaska - Evan L. Salcido; Carena J. van Riper; William P. Stewart; Christopher M. Raymond; Henry S. Pollock (Ambio, 2026)
Diverse values expressed by people living around protected areas provide insight into shared reasons why agreements and tensions may exist yet are underrepresented in research with subsistence users. We administered a mixed-mode survey to residents living near Denali National Park and Preserve and Denali State Park in Interior Alaska, USA, to understand how values placed on landscapes by multiple interest groups could lead to actions benefitting the environment. We discovered four dominant groupings of specific values—centered on pristine nature, communal cohesion, relational fulfillment, and capacity growth—that signaled broad agreement on reasons why Denali landscapes are important. Results from a latent variable path model showed that these values worked in conjunction with previous experience to explain levels of environmental concern, and in turn, pro-environmental behavior. Communal cohesion, in particular, drove subsistence users’ concerns and behaviors, whereas pristine nature was the basis for behavioral decision-making among non-subsistence users.

Species Loss Scenarios Identify Canada's Northern Ecosystems as Disproportionately Vulnerable - Isaac Eckert; Dominique Caron; Laura J. Pollock (Journal of Biogeography, 2026)
Aim Amid ongoing and accelerating global change, predicting the ecological consequences of future species loss is important for prioritising conservation actions to protect biodiversity. Species richness has long been thought to protect communities from species loss by providing ecological redundancy, whereby the loss of any one species hardly impacts the integrity of the wider community due to overlap in species' ecological roles. However, the extent to which species richness will buffer the impacts of future species loss remains unclear due to concurrent variation in both the distribution and ecological roles of species likely to be lost. Location Canada. Taxon Terrestrial vertebrates. Methods To understand how future species loss threatens ecosystems and whether species richness mitigates this threat, we simulated the loss of imperilled taxa from Canadian ecosystems across spatial scales and measured the extent to which community functional and interaction (predator–prey) diversity, two important components of ecosystem integrity, declined. Results We report that, despite harbouring far fewer species at risk, northern ecosystems are disproportionately vulnerable, whereby the loss of imperilled taxa could result in up to 25% and 20% declines in functional and interaction diversity, respectively. Surprisingly, despite high species richness, some southern ecosystems containing high numbers of imperilled taxa were also vulnerable, indicating that richness alone is likely insufficient at predicting community vulnerability to species loss. Main Conclusions Together, these findings demonstrate the need to account for future species loss when evaluating the vulnerability of Earth's ecosystems and highlight the importance of conserving species at risk, specifically in northern communities where they potentially play outsized roles in structuring and maintaining the integrity of ecosystems.

Pairing OpenET remotely sensed evapotranspiration with streamflow data to assess the effectiveness of irrigation curtailment for aquatic conservation - J. Eli Asarian; Bronwen Stanford; Nicholas P. Murphy; Michael M. Pollock (Journal of Hydrology, 2025)

Drifting fish aggregation devices as a tool to study oceanic marine protected areas - Arthur Blanluet; Edward T. Game; Kydd Pollock; Nicholas H. Wolff; Jason D. Everett; Sandra Neubert; Daniel C. Dunn; Anthony J. Richardson (Fisheries Research, 2025)

No species left behind: borrowing strength to map data-deficient species - Shubhi Sharma; Kevin Winner; Laura J. Pollock; James T. Thorson; Jussi Mäkinen; Cory Merow; Eric J. Pedersen; Kalkidan F. Chefira; Julia M. Portmann; Fabiola Iannarilli; Sara Beery; Riccardo de Lutio; et al. (Trends in Ecology & Evolution, 2025)

Traits, Threats, and Popularity Explain Extinction Risk of Birds Globally - Janaína de Andrade Serrano; Lars Iversen; Laura J. Pollock (Global Ecology and Biogeography, 2025)
Aim This study aims to understand how biological traits, human‐induced threats, and species popularity interact to influence the extinction risk of bird species globally. We seek to improve the accuracy of extinction risk assessments and inform conservation strategies. Location Global. Time Period Current. Major Taxa Studied Birds. Methods We predict extinction risk for bird species globally based on relevant biological traits, threats (based on the IUCN Red List), and species popularity estimated from Google search frequency using a Bayesian hierarchical phylogenetic model. Results We find that biological traits, human‐induced threats, and species popularity all explain extinction risk. Some interactions are important (e.g., larger species are more likely threatened by hunting and small‐ranged and migratory species are more threatened by agriculture). We also find that more popular species are more likely to be listed as at risk than unpopular species with similar traits and threats. Main Conclusions Our study highlights the need for incorporating biological traits, anthropogenic threats and human bias into extinction risk assessments. These factors interact in complex ways, influencing the vulnerability of bird species. By accounting for these interactions, conservation efforts can be more effectively targeted to protect species with the highest risk.

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Tempo and mode of diversification of the red devil spiders (Araneae: Dysderidae) of the Canary Islands - Adrià Bellvert; Laura J. Pollock; Antigoni Kaliontzopoulou; Miquel A. Arnedo (Zoologica Scripta, 2025)
The study of adaptive radiations has shed light on our current understanding of evolution. However, previous studies examining the mode in which species diversified, how diversification rates varied, and how ecological specialisation affected these processes have found few different results across different taxa and geographic and ecological systems, showing how complex this process is. To gain a more complete picture of how species evolve, additional model systems that encompass alternative ecological requirements are needed. Here, we present the results of a study aimed at unravelling the diversification mode and evolutionary drivers of the spider genus Dysdera , the red devil spiders, endemic to the Canary Islands. These species exhibit remarkable phenotypic variability in their mouthparts, which has been related to different levels of specialisation in the predation of isopods. We explored patterns of lineage diversification and assessed the role of trophic specialisation as a driver of species diversification. Additionally, we used climatic variables, occurrence data and morphological information to unravel the underlying mode of speciation by means of joint species distribution models and age‐range correlation methods. Our results reveal that red devil spiders underwent an early burst of diversification, followed by a slowdown of diversification rates, which is a hallmark of adaptive radiation. We also found evidence that the trophic morphology shaped diversification, with specialist species exhibiting higher rates of diversification. Finally, our analyses suggest that speciation occurred mostly in allopatry, with subsequent secondary sympatry following range expansion.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Five recommendations to fill the blank space in indicators at local and short-term scales - Katherine Hébert; Maximiliane Jousse; Janaína Serrano; Dirk Nikolaus Karger; F. Guillaume Blanchet; Laura J. Pollock (Biological Conservation, 2025)

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The use of oral fluids and sock samples for monitoring key pathogens in pig populations for surveillance purposes - Joanna Gerszon; Andreas Büchse; Berit Genz; Yvette Pollock; Bernie Gleeson; Andrew Morris; Melony J. Sellars; Ralf J. Moser (Preventive Veterinary Medicine, 2024)

The public–private divide and seasonal variation shape bird diversity in greenspaces of two neighboring midwestern USA cities - Henry S. Pollock; Carena J. van Riper; Devin J. Goodson; Susannah B. Lerman; Mark E. Hauber (Landscape and Urban Planning, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Linking biodiversity, ecosystem function, and Nature’s contributions to people: a macroecological energy flux perspective - Ana Carolina Antunes; Emilio Berti; Ulrich Brose; Myriam R. Hirt; Dirk N. Karger; Louise M.J. O’Connor; Laura J. Pollock; Wilfried Thuiller; Benoit Gauzens (Trends in Ecology & Evolution, 2024)

Trait‐matching models predict pairwise interactions across regions, not food web properties - Dominique Caron; Ulrich Brose; Miguel Lurgi; F. Guillaume Blanchet; Dominique Gravel; Laura J. Pollock (Global Ecology and Biogeography, 2024)
Aim Food webs are essential for understanding how ecosystems function, but empirical data on the interactions that make up these ecological networks are lacking for most taxa in most ecosystems. Trait‐based models can fill these data gaps, but their ability to do so has not been widely tested. We test how well these models can extrapolate to new ecological communities both in terms of pairwise predator–prey interactions and higher level food web attributes (i.e. species position, food web‐level properties). Location Canada, Europe, Tanzania. Time Period Current. Major Taxa Studied Terrestrial vertebrates. Methods We train trait‐based models of pairwise trophic interactions on four independent vertebrate food webs (Canadian tundra, Serengeti, alpine south‐eastern Pyrenees and Europe) and evaluate how well these models predict pairwise interactions and network properties of each food web. Results We find that, overall, trait‐based models predict most interactions and their absence correctly. Performance was best for training and testing on the same food web (AUC > 0.90) and declined with environmental and phylogenetic distances with the strongest loss of performance for the tundra‐Serengeti ecosystems (AUC > 0.75). Network metrics were less well‐predicted than single interactions by our models with predicted food webs being more connected, less modular, and with higher mean trophic levels than observed. Main Conclusions Theory predicts that the variability observed in food webs can be explained by differences in trait distributions and trait‐matching relationships. Our finding that trait‐based models can predict many trophic interactions, even in contrasting environments, adds to the growing body of evidence that there are general constraints on interactions and that trait‐based methods can serve as a useful first approximation of food webs in unknown areas. However, food webs are more than the sum of their parts, and predicting network attributes will likely require models that simultaneously predict individual interactions and community constraints.

Vulnerability of terrestrial vertebrate food webs to anthropogenic threats in Europe - Louise M. J. O'Connor; Francesca Cosentino; Michael B. J. Harfoot; Luigi Maiorano; Chiara Mancino; Laura J. Pollock; Wilfried Thuiller (Global Change Biology, 2024)
Vertebrate species worldwide are currently facing significant declines in many populations. Although we have gained substantial knowledge about the direct threats that affect individual species, these threats only represent a fraction of the broader vertebrate threat profile, which is also shaped by species interactions. For example, threats faced by prey species can jeopardize the survival of their predators due to food resource scarcity. Yet, indirect threats arising from species interactions have received limited investigation thus far. In this study, we investigate the indirect consequences of anthropogenic threats on biodiversity in the context of European vertebrate food webs. We integrated data on trophic interactions among over 800 terrestrial vertebrates, along with their associated human‐induced threats. We quantified and mapped the vulnerability of various components of the food web, including species, interactions, and trophic groups to six major threats: pollution, agricultural intensification, climate change, direct exploitation, urbanization, and invasive alien species and diseases. Direct exploitation and agricultural intensification were two major threats for terrestrial vertebrate food webs: affecting 34% and 31% of species, respectively, they threaten 85% and 69% of interactions in Europe. By integrating network ecology with threat impact assessments, our study contributes to a better understanding of the magnitude of anthropogenic impacts on biodiversity.

Costly inductions as a commitment-selection strategy: Assessing hazing's relationship with attrition in a college fraternity - Aldo Cimino; Joshua Pollock; Benjamin J. Thomas (Evolution and Human Behavior, 2024)

Indicators to monitor the status of the tree of life - Rikki Gumbs; Abhishek Chaudhary; Barnabas H. Daru; Daniel P. Faith; Félix Forest; Claudia L. Gray; Aida Kowalska; Who‐Seung Lee; Roseli Pellens; Sebastian Pipins; Laura J. Pollock; James Rosindell; et al. (Conservation Biology, 2023)
Following the failure to fully achieve any of the 20 Aichi biodiversity targets, the future of biodiversity rests in the balance. The Convention on Biological Diversity's Kunming–Montreal Global Biodiversity Framework (GBF) presents the opportunity to preserve nature's contributions to people (NCPs) for current and future generations by conserving biodiversity and averting extinctions. There is a need to safeguard the tree of life—the unique and shared evolutionary history of life on Earth—to maintain the benefits it bestows into the future. Two indicators have been adopted within the GBF to monitor progress toward safeguarding the tree of life: the phylogenetic diversity (PD) indicator and the evolutionarily distinct and globally endangered (EDGE) index. We applied both to the world's mammals, birds, and cycads to show their utility at the global and national scale. The PD indicator can be used to monitor the overall conservation status of large parts of the evolutionary tree of life, a measure of biodiversity's capacity to maintain NCPs for future generations. The EDGE index is used to monitor the performance of efforts to conserve the most distinctive species. The risk to PD of birds, cycads, and mammals increased, and mammals exhibited the greatest relative increase in threatened PD over time. These trends appeared robust to the choice of extinction risk weighting. EDGE species had predominantly worsening extinction risk. A greater proportion of EDGE mammals (12%) had increased extinction risk compared with threatened mammals in general (7%). By strengthening commitments to safeguarding the tree of life, biodiversity loss can be reduced and thus nature's capacity to provide benefits to humanity now and in the future can be preserved.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Culturing for conservation: the need for timely investments in reef aquaculture - April D. Ridlon; Edwin D. Grosholz; Boze Hancock; Margaret W. Miller; Aric Bickel; Halley E. Froehlich; Diego Lirman; F. Joseph Pollock; Hollie M. Putnam; Michael F. Tlusty; Tiffany J. Waters; Kerstin Wasson (Frontiers in Marine Science, 2023)
Temperate oyster and tropical coral reefs are analogous systems that create habitat for economically, ecologically, and culturally important species, and they provide countless ecosystem services to human coastal communities. Globally, reefs are imperiled by multiple anthropogenic stressors, particularly climate impacts. Using aquaculture to support conservation goals - known as conservation aquaculture - is a relatively new approach for many reef building species, but it shows great promise for promoting species recovery and bolstering resilience to stressors. Concerns about aquaculture-associated risks, both known and potential, have often restricted the implementation of this tool to an emergency intervention following dramatic declines on reefs, when species or systems were unlikely to recover. Here, we combine expertise from coral and oyster reef ecosystems to consider the role of aquaculture as a conservation intervention for reefs, and provide recommendations for its timely development and targeted implementation. We highlight the importance of evaluating reef systems - alongside local stakeholders and Indigenous communities - to determine where and when the benefits of using aquaculture are most likely to outweigh the risks. We spotlight the importance of proactive monitoring to detect reef population declines, and the value of early aquaculture interventions to increase efficacy. Novel aquaculture approaches and technologies specifically designed for reef builders are considered, including techniques for building complex, multi-generational and multi-species reefs. We address the need for scaling up aquaculture-assisted reef recovery, particularly of corals, using high volume methods like those that have been successfully employed for oysters. We also recommend the immediate assessment and development of techniques to increase climate resilience of reef builders and we identify the challenges and trade-offs of these approaches. We highlight the use of proof-of-concept projects to test these promising methods, and we advise tracking of all interventions over time to determine their long-term efficacy. Finally, we outline opportunities to leverage novel partnerships among conservation, industry, and community interests that utilize aquaculture to facilitate the conservation of reefs. Developing conservation aquaculture approaches now is critical to position managers, scientists, and restoration practitioners to implement this intervention in timely and effective ways to support resilient reef and human communities worldwide.

Model training periods impact estimation of COVID-19 incidence from wastewater viral loads - Maria L. Daza-Torres; J. Cricelio Montesinos-López; Minji Kim; Rachel Olson; C. Winston Bess; Lezlie Rueda; Mirjana Susa; Linnea Tucker; Yury E. García; Alec J. Schmidt; Colleen C. Naughton; Brad H. Pollock; et al. (Science of The Total Environment, 2023)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

A phylogenomic examination of Palmyra Atoll’s corallimorpharian invader - Kaitlyn P. Jacobs; Cynthia L. Hunter; Zac H. Forsman; Amanda L. Pollock; Mariana Rocha de Souza; Robert J. Toonen (Coral Reefs, 2022)

Addressing the Eltonian shortfall with trait‐based interaction models - Dominique Caron; Luigi Maiorano; Wilfried Thuiller; Laura J. Pollock (Ecology Letters, 2022)
We have very limited knowledge of how species interact in most communities and ecosystems despite trophic relationships being fundamental for linking biodiversity to ecosystem functioning. A promising approach to fill this gap is to predict interactions based on functional traits, but many questions remain about how well we can predict interactions for different taxa, ecosystems and amounts of input data. Here, we built a new traits‐based model of trophic interactions for European vertebrates and found that even models calibrated with 0.1% of the interactions (100 out of 71 k) estimated the full European vertebrate food web reasonably well. However, predators were easier to predict than prey, especially for some clades (e.g. fowl and storks) and local food web connectance was consistently overestimated. Our results demonstrate the ability to rapidly generate food webs when empirical data are lacking—an important step towards a more complete and spatially explicit description of food webs.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Environmental and anthropogenic constraints on animal space use drive extinction risk worldwide - Myriam R. Hirt; Andrew D. Barnes; Alessandro Gentile; Laura J. Pollock; Benjamin Rosenbaum; Wilfried Thuiller; Marlee A. Tucker; Ulrich Brose (Ecology Letters, 2021)
Animals require a certain amount of habitat to persist and thrive, and habitat loss is one of the most critical drivers of global biodiversity decline. While habitat requirements have been predicted by relationships between species traits and home‐range size, little is known about constraints imposed by environmental conditions and human impacts on a global scale. Our meta‐analysis of 395 vertebrate species shows that global climate gradients in temperature and precipitation exert indirect effects via primary productivity, generally reducing space requirements. Human pressure, however, reduces realised space use due to ensuing limitations in available habitat, particularly for large carnivores. We show that human pressure drives extinction risk by increasing the mismatch between space requirements and availability. We use large‐scale climate gradients to predict current species extinction risk across global regions, which also offers an important tool for predicting future extinction risk due to ongoing space loss and climate change.

Urbanisation weakens selection on the timing of breeding and clutch size in blue tits but not in great tits - Claire J. Branston; Pablo Capilla-Lasheras; Christopher J. Pollock; Kate Griffiths; Stewart White; Davide M. Dominoni (Behavioral Ecology and Sociobiology, 2021)
Urbanisation is a globally occurring phenomenon and is predicted to continue increasing rapidly. Urban ecosystems present novel environments and challenges which species must acclimate or adapt to. These novel challenges alter existing or create new selection pressures on behaviours which provide an opportunity to investigate eco-evolutionary responses to contemporary environmental change. We used 7 years of breeding data from urban and forest populations of blue and great tits to understand whether selection for timing of breeding or clutch size differed between the two habitats and species. We found that urban great tits laid eggs earlier than their forest counterparts, but there was no evidence of a difference in selection for earlier breeding. Blue tits, however, did not differ in timing of egg laying between the two habitats, but selection for earlier laying was weaker in the urban environment. Both species laid smaller clutches in the urban site and had positive selection for larger clutch sizes which did not differ in strength for the great tits but did for blue tits, with weaker selection in the urban population. Our results suggest that food availability for nestlings may be constraining urban birds, and that the temporal cues females use to time breeding correctly, such as tree budburst and food availability, may be absent or reduced in urban areas due to lower caterpillar availability. These results have implications for our understanding of the adaptation of wild animals to city life. Significance statement Urbanisation is expanding rapidly and changing the environment many species live in. A key challenge is to understand how species adapt to the urban environment, why some species can adapt, why others cannot and what we can do to ensure that cities are ecologically sustainable and biodiversity rich. Here we show that the strength of natural selection for early breeding and larger clutch size is weaker in urban than non-urban blue tits, likely due to reduced and irregular availability of natural insect food in urban areas. This effect was not found in great tits. Thus, urbanisation can alter the selection pressures wild animals are exposed to, but this effect may differ between species, even when closely related. This has implications for our understanding of how species adapt to urban life.

Neural correlates of working memory’s suppression of aversive olfactory distraction effects - Alexander Weigard; Stephen J. Wilson; Zvi Shapiro; Hilary Galloway-Long; Cynthia Huang-Pollock (Brain Imaging and Behavior, 2021)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

A Novel Framework to Predict Relative Habitat Selection in Aquatic Systems: Applying Machine Learning and Resource Selection Functions to Acoustic Telemetry Data From Multiple Shark Species - Lucas P. Griffin; Grace A. Casselberry; Kristen M. Hart; Adrian Jordaan; Sarah L. Becker; Ashleigh J. Novak; Bryan M. DeAngelis; Clayton G. Pollock; Ian Lundgren; Zandy Hillis-Starr; Andy J. Danylchuk; Gregory B. Skomal (Frontiers in Marine Science, 2021)
Resource selection functions (RSFs) have been widely applied to animal tracking data to examine relative habitat selection and to help guide management and conservation strategies. While readily used in terrestrial ecology, RSFs have yet to be extensively used within marine systems. As acoustic telemetry continues to be a pervasive approach within marine environments, incorporation of RSFs can provide new insights to help prioritize habitat protection and restoration to meet conservation goals. To overcome statistical hurdles and achieve high prediction accuracy, machine learning algorithms could be paired with RSFs to predict relative habitat selection for a species within and even outside the monitoring range of acoustic receiver arrays, making this a valuable tool for marine ecologists and resource managers. Here, we apply RSFs using machine learning to an acoustic telemetry dataset of four shark species to explore and predict species-specific habitat selection within a marine protected area. In addition, we also apply this RSF-machine learning approach to investigate predator-prey relationships by comparing and averaging tiger shark relative selection values with the relative selection values derived for eight potential prey-species. We provide methodological considerations along with a framework and flexible approach to apply RSFs with machine learning algorithms to acoustic telemetry data and suggest marine ecologists and resource managers consider adopting such tools to help guide both conservation and management strategies.

Dos and don'ts when inferring assembly rules from diversity patterns - Tamara Münkemüller; Laure Gallien; Laura J. Pollock; Ceres Barros; Marta Carboni; Loïc Chalmandrier; Florent Mazel; Karel Mokany; Cristina Roquet; Jan Smyčka; Matthew V. Talluto; Wilfried Thuiller (Global Ecology and Biogeography, 2020)
Aim More than ever, ecologists seek to understand how species are distributed and have assembled into communities using the “filtering framework”. This framework is based on the hypothesis that local assemblages result from a series of abiotic and biotic filters applied to regional species pools and that these filters leave predictable signals in observed diversity patterns. In theory, statistical comparisons of expected and observed patterns enable data‐driven tests of assembly processes. However, so far this framework has fallen short in delivering generalizable conclusions, challenging whether (and how) diversity patterns can be used to characterize and understand underlying assembly processes better. Methods By synthesizing the previously raised critiques and suggested solutions in a comprehensive way, we identify 10 pitfalls that can lead to flawed interpretations of α‐diversity patterns, summarize solutions developed to circumvent these pitfalls and provide general guidelines. Results We find that most issues arise from an overly simplistic view of potential processes that influence diversity patterns, which is often motivated by practical constraints on study design, focal scale and methodology. We outline solutions for each pitfall, such as methods spanning over spatial, environmental or phylogenetic scales, and suggest guidelines for best scientific practices in community ecology. Among key future challenges are the integration of mechanistic modelling and multi‐trophic interactions. Main conclusions Our conclusion is that the filtering framework still holds promise, but only if researchers successfully navigate major pitfalls, foster the integration of mechanistic modelling and multi‐trophic interactions and directly account for uncertainty in their conclusions.

Knee extension with blood flow restriction: Impact of cuff pressure on hemodynamics - Tyler J. Singer; Jon Stavres; Steven J. Elmer; Matthew A. Kilgas; Brandon S. Pollock; Sarah G. Kearney; John McDaniel (European Journal of Applied Physiology, 2020)

Coarse- and fine-scale acoustic telemetry elucidates movement patterns and temporal variability in individual territories for a key coastal mesopredator - Sarah L. Becker; John T. Finn; Ashleigh J. Novak; Andy J. Danylchuk; Clayton G. Pollock; Zandy Hillis-Starr; Ian Lundgren; Adrian Jordaan (Environmental Biology of Fishes, 2020)

Productivity begets less phylogenetic diversity but higher uniqueness than expected - Wilfried Thuiller; Dominique Gravel; Gentile Francesco Ficetola; Sébastien Lavergne; Tamara Münkemüller; Laura J. Pollock; Niklaus E. Zimmermann; Florent Mazel (Journal of Biogeography, 2020)
Aim The positive effect of primary productivity on animal species richness is one of the most conspicuous ecological features on Earth. However, less is known about the relationship between ecosystems primary productivity and the evolutionary history of biota. Here, we analyse how global primary productivity relates to the phylogenetic structure of vertebrate assemblages, and to the distribution of the most distinct lineages and recently diversified clades. Location Global. Taxon Amphibians, birds and mammals. Methods We calculated relative phylogenetic diversity (i.e. phylogenetic diversity corrected for species richness), standardized effect size of the richness of top 25% evolutionary distinct species and of top 25% species‐level lineage diversification rates. We related these three metrics to mean net primary productivity (NPP) at the global scale, and for each zoogeographic region. We also tested the influence of the spatial scaling of species pool on the overall analyses (global, hemispheric and zoogeographic regions‐based species pools). Results Phylogenetic diversity (corrected for species richness) of the three taxa decreases with NPP (in contrast with species richness) and varies considerably in space. High productivity sites harbour more closely related species than low productivity sites consistently across zoogeographic zones. However, the phylogenetically most distinct species are also found in high productivity sites, while the top most rapidly diversifying lineages are found in the least productive sites. Modifying the spatial extent of the species pool did not affect the results much. Conclusions Benign conditions in high productivity sites (a) result in denser niche packing and thus allow for the coexistence of many closely‐related species and (b) protect the persistence of evolutionary distinct species. Low productivity sites may harbour fewer, more distinct and temporarily more variable niches that allow maintenance of unique lineages for longer periods of time.

Unveiling the food webs of tetrapods across Europe through the prism of the Eltonian niche - Louise M. J. O’Connor; Laura J. Pollock; João Braga; Gentile Francesco Ficetola; Luigi Maiorano; Camille Martinez‐Almoyna; Alessandro Montemaggiori; Marc Ohlmann; Wilfried Thuiller (Journal of Biogeography, 2020)
Aim Despite recent calls for integrating interaction networks into the study of large‐scale biodiversity patterns, we still lack a basic understanding of the functional characteristics of large interaction networks and how they are structured across environments. Here, building on recent advances in network science around the Eltonian niche concept, we aim to characterize the trophic groups in a large food web, and understand how these trophic groups vary across space. Location Europe and Anatolia. Taxon Tetrapods (1,136 species). Methods We combined an expert‐based metaweb of all European tetrapods with their spatial distributions and biological traits. To understand the functional structure of the metaweb, we first used a stochastic block model to group species with similar Eltonian niches, and then analysed these groups with species’ functional traits and network metrics. We then combined these groups with species distributions to understand how trophic diversity varies across space, in function of the environment, and between the European ecoregions. Results We summarized the 1,136 interacting species within the metaweb into 46 meaningful trophic groups of species with a similar role in the metaweb. Specific aspects of the ecology of species, such as their activity time, nesting habitat and diet explained these trophic groups. Across space, trophic diversity was driven by both biotic and abiotic factors (species richness, climate and primary productivity), and the representation of trophic groups differed among European ecoregions. Main conclusions We have characterized the Eltonian niche of species in a large food web, both in terms of species interactions and functional traits, and then used this to understand the spatial variation of food webs at a functional level, thus bringing together network science, functional ecology and biogeography. Our results highlight the need to integrate multiple aspects of species ecology in global change research. Further, our approach is strongly relevant for conservation biology as it could help predict the impact of species translocations on trophic diversity.

Spatial analyses of multi‐trophic terrestrial vertebrate assemblages in Europe - João Braga; Laura J. Pollock; Ceres Barros; Núria Galiana; José M. Montoya; Dominique Gravel; Luigi Maiorano; Alessandro Montemaggiori; Gentile Francesco Ficetola; Stéphane Dray; Wilfried Thuiller (Global Ecology and Biogeography, 2019)
Aim Although much has been said on the spatial distribution of taxonomic and phylogenetic diversity of vertebrates, how this diversity interacts in food webs and how these interactions change across space are largely unknown. Here, we analysed the spatial distribution of tetrapod food webs and asked whether the variation in local food web structure is driven by random processes or by natural and anthropogenic factors. Location Europe. Time period Present. Major taxa studied Tetrapods. Methods We combined an expert‐based food web (1,140 species and 70,601 links) of all European tetrapods with their respective spatial distributions. We mapped 17 different food web metrics representing complexity, chain length, vertical diversity and diet strategy across Europe and tested whether their distribution reflects the spatial structure of species richness using a null model of food web structure. To avoid multicollinearity issues, we defined composite descriptors of food web structure that we related to a set of environmental layers summarizing both natural and anthropogenic influences and tested their relative importance in explaining the spatial distribution of European terrestrial vertebrate food webs. Results Of the 17 metrics, 10 showed a non‐random spatial distribution across Europe and could be summarized along two major axes of variation in food web structure. The first was related to species richness, mean trophic level and the proportion of intermediate species, whereas the second was related to the connectance and proximity of species within the web. Both descriptors varied with latitudinal gradient. The best descriptors of food web structure were mean annual temperature and seasonality (negatively correlated with the first axis), and human footprint (positively correlated with the second axis). Main conclusions We demonstrate the importance of climate and anthropogenic pressure in shaping the spatial structure of European tetrapod food webs.

Inherited alterations of TGF beta signaling components in Appalachian cervical cancers - Thomas J. Knobloch; Juan Peng; Erinn M. Hade; David E. Cohn; Mack T. Ruffin; Michael A. Schiano; Byron C. Calhoun; William C. McBee; Jamie L. Lesnock; Holly H. Gallion; Jondavid Pollock; Bo Lu; et al. (Cancer Causes & Control, 2019)

Inferring pyroclastic density current flow conditions using syn-depositional sedimentary structures - Nicholas M. Pollock; Brittany D. Brand; Peter J. Rowley; Damiano Sarocchi; Roberto Sulpizio (Bulletin of Volcanology, 2019)

Limb blood flow and tissue perfusion during exercise with blood flow restriction - Matthew A. Kilgas; John McDaniel; Jon Stavres; Brandon S. Pollock; Tyler J. Singer; Steven J. Elmer (European Journal of Applied Physiology, 2019)

A cognitive model-based approach to testing mechanistic explanations for neuropsychological decrements during tobacco abstinence - Alexander Weigard; Cynthia Huang-Pollock; Andrew Heathcote; Larry Hawk; Nicolas J. Schlienz (Psychopharmacology, 2018)

Ranking composite Cancer Burden Indices for geographic regions: point and interval estimates - Bin Huang; Elizabeth Pollock; Li Zhu; Jessica P. Athens; Ron Gangnon; Eric J. Feuer; Thomas C. Tucker (Cancer Causes & Control, 2018)

Generation of transgenic goats by pronuclear microinjection: a retrospective analysis of a commercial operation (1995–2012) - W. Gavin; S. Blash; N. Buzzell; D. Pollock; L. Chen; N. Hawkins; J. Howe; K. Miner; J. Pollock; C. Porter; M. Schofield; Y. Echelard; et al. (Transgenic Research, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Assessing coral health and disease from digital photographs and in situ surveys - C. A. Page; S. N. Field; F. J. Pollock; J. B. Lamb; G. Shedrawi; S. K. Wilson (Environmental Monitoring and Assessment, 2017)

Experimental and theoretical correlations between vanadium K-edge X-ray absorption and K $$\varvec{β} $$ β emission spectra - Julian A. Rees; Aleksandra Wandzilak; Dimitrios Maganas; Nicole I. C. Wurster; Stefan Hugenbruch; Joanna K. Kowalska; Christopher J. Pollock; Frederico A. Lima; Kenneth D. Finkelstein; Serena DeBeer (JBIC Journal of Biological Inorganic Chemistry, 2016)

A Full-Capture Hierarchical Bayesian Model of Pollock's Closed Robust Design and Application to Dolphins - Robert W. Rankin; Krista E. Nicholson; Simon J. Allen; Michael Krützen; Lars Bejder; Kenneth H. Pollock (Frontiers in Marine Science, 2016)

Sex-Specific Patterns in Abundance, Temporary Emigration and Survival of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) in Coastal and Estuarine Waters - Kate R. Sprogis; Kenneth H. Pollock; Holly C. Raudino; Simon J. Allen; Anna M. Kopps; Oliver Manlik; Julian A. Tyne; Lars Bejder (Frontiers in Marine Science, 2016)

Site-Specific Assessments of the Abundance of Three Inshore Dolphin Species to Inform Conservation and Management - Alexander M. Brown; Lars Bejder; Kenneth H. Pollock; Simon J. Allen (Frontiers in Marine Science, 2016)

From species distributions to meta‐communities - Wilfried Thuiller; Laura J. Pollock; Maya Gueguen; Tamara Münkemüller (Ecology Letters, 2015)
The extent that biotic interactions and dispersal influence species ranges and diversity patterns across scales remains an open question. Answering this question requires framing an analysis on the frontier between species distribution modelling ( SDM ), which ignores biotic interactions and dispersal limitation, and community ecology, which provides specific predictions on community and meta‐community structure and resulting diversity patterns such as species richness and functional diversity. Using both empirical and simulated datasets, we tested whether predicted occurrences from fine‐resolution SDM s provide good estimates of community structure and diversity patterns at resolutions ranging from a resolution typical of studies within reserves (250 m) to that typical of a regional biodiversity study (5 km). For both datasets, we show that the imprint of biotic interactions and dispersal limitation quickly vanishes when spatial resolution is reduced, which demonstrates the value of SDM s for tracking the imprint of community assembly processes across scales.

Integrating acoustic telemetry into mark–recapture models to improve the precision of apparent survival and abundance estimates - Christine L. Dudgeon; Kenneth H. Pollock; J. Matias Braccini; Jayson M. Semmens; Adam Barnett (Oecologia, 2015)

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain - F. Joseph Pollock; Cory J. Krediet; Melissa Garren; Roman Stocker; Karina Winn; Bryan Wilson; Carla Huete-Stauffer; Bette L. Willis; David G. Bourne (Coral Reefs, 2015)

Towards a better understanding of white syndromes and their causes on Indo-Pacific coral reefs - D. G. Bourne; T. D. Ainsworth; F. J. Pollock; B. L. Willis (Coral Reefs, 2015)

Adding value to rare tissue samples donated to biobanks: characterisation of breast tissue and primary cell cultures obtained from a female-to-male transgender patient - Rebecca Millican-Slater; Rona Good; Claire Nash; Judith A. Heads; Steven Pollock; Rebecca Chalkley; Jenny Gomm; J. Louise Jones; Sreekumar Sundara-Rajan; Kieran Horgan; Andrew M. Hanby; Valerie Speirs (Cell and Tissue Banking, 2015)

Population dynamics of the reef manta ray Manta alfredi in eastern Australia - L. I. E. Couturier; C. L. Dudgeon; K. H. Pollock; F. R. A. Jaine; M. B. Bennett; K. A. Townsend; S. J. Weeks; A. J. Richardson (Coral Reefs, 2014)

Cardiovascular responses to counterweighted single-leg cycling: implications for rehabilitation - Keith J. Burns; Brandon S. Pollock; Phil LaScola; John McDaniel (European Journal of Applied Physiology, 2014)

Cold habituation does not improve manual dexterity during rest and exercise in 5 °C - Matthew D. Muller; Yongsuk Seo; Chul-Ho Kim; Edward J. Ryan; Brandon S. Pollock; Keith J. Burns; Ellen L. Glickman (International Journal of Biometeorology, 2014)

Cymo melanodactylus crabs slow progression of white syndrome lesions on corals - F. J. Pollock; S. M. Katz; D. G. Bourne; B. L. Willis (Coral Reefs, 2013)

A spatial mark–resight model augmented with telemetry data - Rahel Sollmann; Beth Gardner; Arielle W. Parsons; Jessica J. Stocking; Brett T. McClintock; Theodore R. Simons; Kenneth H. Pollock; Allan F. O'Connell (Ecology, 2013)
Abundance and population density are fundamental pieces of information for population ecology and species conservation, but they are difficult to estimate for rare and elusive species. Mark–resight models are popular for estimating population abundance because they are less invasive and expensive than traditional mark–recapture. However, density estimation using mark–resight is difficult because the area sampled must be explicitly defined, historically using ad hoc approaches. We developed a spatial mark–resight model for estimating population density that combines spatial resighting data and telemetry data. Incorporating telemetry data allows us to inform model parameters related to movement and individual location. Our model also allows Procyon lotor ) on South Core Banks, a barrier island in Cape Lookout National Seashore, North Carolina, USA. We estimated a population of 186.71 ± 14.81 individuals, which translated to a density of 8.29 ± 0.66 individuals/km 2 (mean ± SD). The model presented here will have widespread utility in future applications, especially for species that are not naturally marked.

Chloroplast DNA diversity associated with protected slopes and valleys for hybridizing Eucalyptus species on isolated ranges in south‐eastern Australia - Laura J. Pollock; Michael J. Bayly; Paul G. Nevill; Peter A. Vesk (Journal of Biogeography, 2013)
Aim To relate genetic diversity to topographic features and to investigate genetic interactions between Eucalyptus species in a local centre of endemism and diversity in south‐eastern Australia. Location Grampian Ranges, Victoria, Australia. Methods We documented chloroplast DNA (cpDNA) variation for a group of endemic Eucalyptus species ( E. serraensis, E. verrucata and E. victoriana ) that dominate rocky, high‐elevation ridgelines of the Grampian Ranges and for one closely‐related, widespread species ( E. baxteri ) occupying flanking slopes and valleys. We documented genetic patterns across the landscape using cpDNA microsatellites, and related them to topographic features (exposed west‐facing versus protected east‐facing slopes and valleys). We also determined the extent of local haplotype sharing between populations of endemic species and neighbouring E. baxteri downslope with cpDNA microsatellites, and haplotype sharing between the endemic group and more distantly related species ( E. obliqua , E. pauciflora and E. willisii ) with sequences of the J LA + chloroplast region. Results We detected 26 cpDNA microsatellite haplotypes in a relatively small area of c . 20 km × 50 km. Populations of E. baxteri on east‐facing slopes and valleys had greater cpDNA microsatellite diversity than E. baxteri and endemic species on exposed west‐facing slopes. Endemic species frequently shared chloroplast haplotypes with E. baxteri downslope. Sharing of J LA + haplotypes with species outside the endemic group was mostly restricted to E. victoriana , which had cpDNA more similar to the species from other sections of Eucalyptus ( E. obliqua , E. willisii and E. pauciflora ). Main conclusions Intensive sampling of related species on small isolated mountain ranges allowed us to relate genetic diversity to fine‐scale habitats and to document extensive local haplotype sharing between species. This study contributes to a general understanding of the environmental conditions that enable plant population persistence by linking concentrations of genetic diversity to particular habitats.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Application of a single-objective, hybrid genetic algorithm approach to pharmacokinetic model building - Eric A. Sherer; Mark E. Sale; Bruce G. Pollock; Chandra P. Belani; Merrill J. Egorin; Percy S. Ivy; Jeffrey A. Lieberman; Stephen B. Manuck; Stephen R. Marder; Matthew F. Muldoon; Howard I. Scher; David B. Solit; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Sports and hybrids of triploid Hosta ‘Sum and Substance’ reveal chromosome losses and gains in all three apical layers - B. J. M. Zonneveld; W. I. Pollock (Plant Systematics and Evolution, 2012)

Do fathead minnows, Pimephales promelas Rafinesque, alter their club cell investment in responses to variable risk of infection from Saprolegnia ? - R J Pollock; M S Pollock; M C O Ferrari; S G W Kaminskyj; D P Chivers (Journal of Fish Diseases, 2012)
Fish in the Superorder Ostariophysi possess large epidermal club cells that release chemical cues warning nearby conspecifics of danger. Despite the long‐held assumption that such club cells evolved under the selective force of predation, recent studies demonstrated that predation has no effect on club cell investment. Rather, club cells have an immune function and cell production may be stimulated by skin‐penetrating pathogens and parasites. The current work investigates whether fathead minnows, Pimephales promelas , alter their club cell characteristics based on variation in infection risk. In a 2 × 3 design, we exposed minnows to infective cysts of two oomycete species ( Saprolegnia ferax and S. parasitica ) at three different concentrations (2, 20 or 200 cysts L −1 ). Club cell characteristics (number and size) were quantified 12 days after exposure. Saprolegnia parasitica is thought to be more pathogenic than S. ferax , hence we predicted greater club cell investment and a larger turnover rate of cells by minnows exposed to S. parasitica than S. ferax. We also predicted that minnows exposed to higher numbers of cysts should invest more in club cells and have a higher turnover rate of cells. We found no difference in club cell density or size between fish exposed to the two Saprolegnia species; however, fish exposed to high concentrations of pathogens had smaller club cells than those exposed to low concentrations, indicating a higher rate of turnover of cells in the epidermis.

The effects of whole body vibration on balance, joint position sense and cutaneous sensation - Ross D. Pollock; Sally Provan; Finbarr C. Martin; Di J. Newham (European Journal of Applied Physiology, 2011)

Do light and alfalfa responses to cloth and slatted shade represent those measured under an agroforestry system? - A. C. Varella; D. J. Moot; K. M. Pollock; P. L. Peri; R. J. Lucas (Agroforestry Systems, 2011)

Groundwater interaction with surface drains in the Ord River Irrigation Area, northern Australia: investigation by multiple methods - Anthony J. Smith; Daniel W. Pollock; Duncan Palmer (Hydrogeology Journal, 2010)

Evaluation of pulsed high intensity focused ultrasound exposures on metastasis in a murine model - Hilary Hancock; Matthew R. Dreher; Nigel Crawford; Claire B. Pollock; Jennifer Shih; Bradford J. Wood; Kent Hunter; Victor Frenkel (Clinical & Experimental Metastasis, 2009)

Soil moisture and water use by pastures and silvopastures in a sub-humid temperate climate in New Zealand - K. M. Pollock; Donald J. Mead; B. A. McKenzie (Agroforestry Systems, 2009)

Influence of pasture understoreys and tree management on soil moisture under a young New Zealand stand of Pinus radiata - K. M. Pollock; D. J. Mead (Plant and Soil, 2008)

Synthesis and pharmacological evaluation of m-terphenyl amines as cyclooxygenase inhibitors - John D. Bauer; Michael S. Foster; Jeffrey D. Hugdahl; Kristi L. Burns; Sheldon W. May; Stanley H. Pollock; Horace G. Cutler; Stephen J. Cutler (Medicinal Chemistry Research, 2007)

Floral and faunal differences between fragmented and unfragmented bahamian tidal creeks - Lori Valentine-Rose; Julia A. Cherry; J. Jacob Culp; Kathryn E. Perez; Jeff B. Pollock; D. Albrey Arrington; Craig A. Layman (Wetlands, 2007)

Water potential and gas exchange did not reflect performance of Pinus radiata D. Don in an agroforestry system under conditions of soil-water deficit in a temperate environment - Isa A. M. Yunusa; Sue E. Thomson; Keith P. Pollock; Lu Youwei; Donald J. Mead (Plant and Soil, 2005)

Giardia surveillance in Scotland, 1988–2003 - K. G. J. Pollock; H. V. Smith; D. Young; C. N. Ramsay; W. J. Reilly (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

US Energy Conservation and Efficiency: Benefits and Costs - D. Pimentel; A. Pleasant; J. Barron; J. Gaudioso; N. Pollock; E. Chae; Y. Kim; A. Lassiter; C. Schiavoni; A. Jackson; M. Lee; A. EATON (Environment, Development and Sustainability, 2004)

Synergistic interactions between chemical alarm cues and the presence of conspecific and heterospecific fish shoals - Brian D. Wisenden; Mike S. Pollock; Robyn J. Tremaine; Jeff M. Webb; Monique E. Wismer; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2003)

Tamoxifen inhibits Ca2+ uptake by the cardiac sarcoplasmic reticulum - Margaret E. Kargacin; Zenobia Ali; Christopher A. Ward; Natashka S. Pollock; Gary J. Kargacin (Pflügers Archiv - European Journal of Physiology, 2000)

Neuroblastoma and parental occupation - Andrew F. Olshan; Anneclaire J. De Roos; Kay Teschke; Joseph P. Neglia; Daniel O. Stram; Brad H. Pollock; Robert P. Castleberry (Cancer Causes & Control, 1999)

Pharmacological evaluation of 1-(carboxymethyl)-3,5-diphenyl-2-methylbenzene, a novel arylacetic acid with potential anti-inflammatory properties - S. J. Cutler; C. DeWitt Blanton Jr.; D. T. Akin; F. B. Steinberg; A. B. Moore; J. A. Lott; T. C. Price; S. W. May; S. H. Pollock (Inflammation Research, 1998)

Physiological changes in extracellular sodium directly control human proximal tubule growth and transport - David W. Johnson; Heather J. Saunders; Philip Poronnik; David I. Cook; Michael J. Field; Carol A. Pollock (Pflügers Archiv - European Journal of Physiology, 1997)

Process studies in aPinus radiata-pasture agroforestry system in a subhumid temperature environment. II. Analysis of dry matter yields in the third year - I. A. M. Yunusa; D. J. Mead; R. J. Lucas; K. M. Pollock (Agroforestry Systems, 1995)

Process studies in aPinus radiata-pasture agroforestry system in a subhumid temperature environment. I. Water use and light interception in the third year - I. A. M. Yunusa; D. J. Mead; K. M. Pollock; R. J. Lucas (Agroforestry Systems, 1995)

Electrophoretic analysis of proteins from night-blind mutants of Phycomyces - J. A. Pollock; E. D. Lipson; D. T. Sullivan (Biochemical Genetics, 1985)